TNFAIP3 Plays a Role in Aging of the Hematopoietic System - Smith, Molly A.; Culver-Cochran, Ashley E.; Adelman, Emmalee R.; Rhyasen, Garrett W.; Ma, Averil; Figueroa, Maria E.; Starczynowski, Daniel T. (Frontiers in Immunology, 2020)
Hematopoietic stem and progenitor cells (HSPC) experience a functional decline in response to chronic inflammation or aging. Haploinsufficiency of A20, or TNFAIP3, an innate immune regulator, is associated with a variety of autoimmune, inflammatory, and hematologic malignancies. Based on a prior analysis of epigenomic and transcriptomic changes during normal human aging, we find that the expression of A20 is significantly reduced in aged HSPC as compared to young HSPC. Here, we show that the partial reduction of A20 expression in young HSPC results in characteristic features of aging. Specifically, heterozygous deletion of A20 in hematopoietic cells resulted in expansion of the HSPC pool, reduced HSPC fitness, and myeloid-biased hematopoiesis. These findings suggest that altered expression of A20 in HSPC contributes to an aging-like phenotype, and that there may be a common underlying mechanism for diminished HSPC function between inflammatory states and aging.